The prevalence and clinical profile of dry eye in tertiary hospital based normal healthy population in Uttarakhand, India - Baisoya, Pooja; Raj, Anuradha; Bahadur, Harsh; Nagpal, R. C. (International Journal Of Community Medicine And Public Health, 2016)
Background: Dry eye is a multifactorial disorder of the tear film due to lack of tears or its excessive evaporation which can potentially damage the ocular surface and is associated with symptoms of ocular discomfort as defined by the National Eye Institute (NEI) Industry workshop in 1995. Objective of the study was to study the prevalence and the clinical profile of dry eye in hospital-based normal healthy population. Methods: In this observational study, 503 patients were screened for dry eye on the basis of questionnaire adopted from Dry Eye Workshop questionnaire which included five symptoms. On the basis of two or more than two symptoms, patients were divided into two groups Group I and Group II respectively. All patients underwent routine ophthalmological examination along with evaluation of tear parameters like Schirmer’s test I, tear film break-up time, slit lamp assisted tear meniscus height measurement, Rose Bengal staining and tear film thinning time. On the basis of questionnaire and tear parameters, 235 patients were found eligible for the study. Final grading of dry eye into four grades was done according to Dry Eye Workshop. Severity of dry eye was divided into three grades as mild, moderate and severe with total score of <3, 3-4, >4 respectively. The data was analysed by using Pearson’s correlation of coefficient and multiple comparison tests with SPSS 22 version. P value<0.05 was taken statistically significant. Results: The prevalence of dry eye in our study was found to be 46.71%. Mean age of the patients was 47.80±16.37 years. Mild, moderate and severe dry eye was seen in 136 (57.87%), 92 (39.14%) and 3 (1.27%) patients respectively. Mean standard value of Schirmer’s test I , tear film break-up time, tear meniscus height and tear film thinning time were 13.59±6.65, 9.66±2.45, 0.39±0.15 and 10.15±2.24 respectively. The P values of all tear parameters were 0.001 which were statistically significant. Conclusions: Dry eye disease prevales to greater extent even in asymptomatic healthy patients and its reliable diagnosis can be done on the basis of both symptoms and tear parameters. Screening of symptomatic patients without any sign of dry eye in the preclinical phase is important for its early detection.